Synergistic effects of foliar potassium supplementation with photoperiod on storage tolerance and taste of fresh cut lettuce - Wang, Wenyuan; Rehman, Muhammad Mahmood Ur; Liu, Jizhan; Wu, Shuo; Zhao, Shengyi (Frontiers in Plant Science, 2025)
Fresh cut lettuce (Lactuca sativa L.) is an important leafy vegetable, due to high perishability, storage tolerance become a critical factor to maintain its quality and taste. This study aimed to determine whether photoperiod duration and potassium fertilizer will boost the taste and the storage tolerance of fresh cut lettuce. A factorial experiment comprising two factors was conducted, involving two photoperiod durations (14h light/day and 12h light/day) and various concentrations of potassium fertilizer (0%, 0.3%, 0.6% and 0.9%) as foliar sprays. For fresh cut lettuce cultivated under a 14-hour photoperiod, applying either 0% or 0.3% potassium enhanced water content, soluble solids accumulation, supported the maintenance of antioxidant enzyme activity stability, and reduced the decay rate during storage. While 0.3% or 0.6% potassium concentration was required to achieve the high quality and storability aim under 12h photoperiod. Current findings may provide a valuable information toward sustainable strategies for enhancing the post-harvest life of fresh cut lettuce with maintained taste and its potential application in post-harvest management of commercial produce.